PENGEMBANGAN INOVASI PRODUK BERKELANJUTAN PADA UKM BU ERMA DI JAMBI - Rodhiah, Rodhiah; Ika Widyani, Agustina; Winduwati, Septia (Transpublika Publisher, 2021)
An entrepreneur must always innovate, so that the products created can face increasingly tough competitive conditions. The partner who became the venue for the activity was Ms. Erma's SME, which is located in Jambi. From the results of initial online observations, it can be seen that the main problem faced by partners is innovation, there is no partner understanding about the importance of sustainable innovation strategies in doing business. This condition occurs because partners lack knowledge about innovation. So that the products produced by partners are monotonous and less innovative, even many are similar to competitors. The activity method is carried out by socializing or providing training to partners online via Zoom. Submission of materials is presented in the form of PPT related to the innovation strategy. The results of the activity showed that the provision of knowledge about innovation had run smoothly, partners were enthusiastic in listening to the material and discussing with the PKM (Student Creativity Program) Team. Furthermore, through innovation, partners can create products into products that can improve business sustainability.